Hypertriglyceridemia Induced by Fluorouracil: A Novel Case Report - Yoshitaka Saito; Yoh Takekuma; Satoshi Yuki; Yoshito Komatsu; Mitsuru Sugawara (Case Reports in Oncology, 2021)
We had previously reported on S-1-induced hypertriglyceridemia. Here, we report fluorouracil-induced hypertriglyceridemia in a patient with capecitabine-induced hypertriglyceridemia and the corresponding therapeutic process. A woman in her forties who had experienced grade 3 hypertriglyceridemia due to oxaliplatin + capecitabine was administered fluorouracil ± oxaliplatin + levofolinate calcium + panitumumab; however, grade 4 hypertriglyceridemia occurred after the thirteenth administration. Bezafibrate normalized the elevation. Chemotherapy cessation resulted in its decrease to normal, and bezafibrate was stopped. Nine months after cessation, treatment with fluorouracil + irinotecan + levofolinate calcium + ramucirumab was initiated. After four cycles of treatment, her serum triglyceride levels increased again to grade 3, and then, fenofibrate was administered, resulting in a significant decrease to grade 1–2. Serum triglyceride levels significantly reduced after cessation of the prior fluorouracil-containing regimen, although its elevation was observed again following the latter treatment. Therefore, fluorouracil-induced hypertriglyceridemia was strongly speculated in this case. We have speculated that the most probable cause of tegafur and capecitabine-induced hypertriglyceridemia is fluorouracil or its metabolic enzymes since their end product is fluorouracil in the previous report. Results from this patient suggest that our supposition was correct. Fibrates administration, cessation of the treatment, and monitoring of serum triglyceride level was effective in this case as well as previous reports. Fluorouracil-induced hypertriglyceridemia is associated with the one caused by tegafur and capecitabine and presents the possibility of severe complications. Elucidation of its exact mechanism and epidemiological features is needed for better understanding.